2020
DOI: 10.3746/pnf.2020.25.2.113
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Gut Microbiome on Obesity in Adults and the Role of Probiotics, Prebiotics, and Synbiotics for Weight Loss

Abstract: The link between the gut microbiome and obesity is not well defined. Understanding of the role of the gut microbiome in weight and health management may lead to future revolutionary changes for treating obesity. This review examined the relationship between obesity and the gut microbiome, and the role of probiotics, prebiotics, and synbiotics for preventing and treating obesity. We used PubMed and Google Scholar to collect appropriate articles for the review. We showed that the gut microbiome has an impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(134 citation statements)
references
References 78 publications
(147 reference statements)
3
127
1
3
Order By: Relevance
“…Interventions modulating the gut bacterial composition in overweight/obese subjects have shown some beneficial metabolic effects (primarily, short‐lasting improvements in insulin resistance), but, as shown in a recent meta‐analysis investigating the effect of faecal microbiota transplantation as a gut microbial‐modulation strategy in obese individuals, no effects on BMI have been shown in any clinical studies 188 . Nevertheless, several studies suggest that gut microbiota and its products may affect the secretion of gut hormones with established effects on hunger and satiety sensations in humans, for example, GLP‐1 and PYY, 189,190 but the pathophysiological implications and therapeutic potential of these interactions remain obscure. Taken together, human obesity is characterized by distinct changes in gut bacteria composition, but the causality and clinical implications of these changes are unclear and there are no data to support that modulation of the gut microbiota in humans has effects on eating behaviour or REE.…”
Section: Pathophysiology Of Obesity In Humansmentioning
confidence: 99%
“…Interventions modulating the gut bacterial composition in overweight/obese subjects have shown some beneficial metabolic effects (primarily, short‐lasting improvements in insulin resistance), but, as shown in a recent meta‐analysis investigating the effect of faecal microbiota transplantation as a gut microbial‐modulation strategy in obese individuals, no effects on BMI have been shown in any clinical studies 188 . Nevertheless, several studies suggest that gut microbiota and its products may affect the secretion of gut hormones with established effects on hunger and satiety sensations in humans, for example, GLP‐1 and PYY, 189,190 but the pathophysiological implications and therapeutic potential of these interactions remain obscure. Taken together, human obesity is characterized by distinct changes in gut bacteria composition, but the causality and clinical implications of these changes are unclear and there are no data to support that modulation of the gut microbiota in humans has effects on eating behaviour or REE.…”
Section: Pathophysiology Of Obesity In Humansmentioning
confidence: 99%
“…Microbiota alteration, known as dysbiosis, has been involved in various diseases. An impaired intestinal flora has been proven to represent a developmental factor in obesity and metabolic syndrome, leading to type 2 diabetes and various cardiovascular impairments [73].…”
Section: Role Of Gut Microbiota In Health and Diseasementioning
confidence: 99%
“…Several studies have shown that obesity is associated with gut microbial dysbiosis [ 5 , 6 ]. The contribution of the microbiome to obesity has been considered using multifactorial approaches, such as supplying additional calories to the host, affecting satiety, favoring fat storage, and disrupting the integrity of the epithelial barrier [ 7 ]. Recently, many studies, regarding weight loss interventions in adults, have investigated the relationship between the gut microbiota and obesity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%